Zidovudine-Loaded PLA and PLA-PEG Blend Nanoparticles: Influence of Polymer Type on Phagocytic Uptake by Polymorphonuclear Cells - Mainardes, Rubiana Mara; Gremião, Maria Palmira Daflon [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Fonseca, Luiz Marcos da [UNESP]; Khalil, Najeh Maissar (John Wiley & Sons Inc, 2009)
Mononuclear (macrophages) and polymorphonuclear leucocytes cells play an important role in the immunopathogenesis of acquired immunodeficiency syndrome. Zidovudine is a broad-spectrum drug used in current antiretroviral therapy. The development of controlled drug delivery systems for the treatment of chronic diseases is of great interest since these systems can act as vectors, carrying the drug only to the target, and the adverse effects can be reduced. In this study, PLA and PLA/PEG blend nanoparticles containing zidovudine were developed and their uptake by polymorphonuclear leucocytes were studied in vitro. The influence of polymer type on particle size, Zeta potential and particle uptake by polymorphonuclear leucocytes was investigated. The cells were isolated from rat peritoneal exudate and their activation by nanoparticles was measured by luminol-dependent chemiluminescence and microscopical analysis. The PEG in the blend modified the Zeta potential suggested the formation of a PEG coat on the particle surface. The phagocytosis depended on the PEG and its ratio in the blend, the results showed that the PLA nanoparticles were more efficiently phagocytosed than PLA/PEG blends. The blend with the highest PEG proportion did not prevent phagocytosis, indicating that the steric effect of PEG was concentration dependent. (C) 2008 Wiley-Liss, Inc. and the American Pharmacists Association J Pharm Sci 98:257-267, 2009
Keywords: zidovudine; chemiluminescence; nanoparticles; phagocytosis